HAKIKAT KURIKULUM DALAM PENDIDIKAN - Abdul Juki Ripandi (Jurnal Al Wahyu, 2023)
Curriculum serves as the essential foundation in the educational context, playing a vital role in shaping the learning process. This article explores the essence of curriculum with a focus on its functions, roles, and position in achieving educational objectives.Firstly, the article discusses the function of the curriculum as the main guide in determining what, how, and when learning materials are presented to students. This function encompasses the role of the curriculum as a tool to achieve national educational goals and develop essential skills for learners.Next, the role of the curriculum is explained through the perspectives of teachers and students. Teachers, as implementers of the curriculum, play a key role in transferring knowledge, shaping skills, and guiding the character development of students. Meanwhile, students, as learning subjects, absorb curriculum content to develop personal understanding and skills.Then, the position of the curriculum within the framework of national and global education becomes the focus of the study. How the curriculum reflects local cultural values while integrating global dimensions is an integral part of this approach.This research integrates theoretical and practical perspectives to provide a holistic understanding of the essence of the curriculum, explaining how the curriculum is not only a formal document but also a life guide for learners.